EFEK MEDIASI PEMBERDAYAAN PADA PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP PERILAKU KEWARGAAN ORGANISASIONAL - Muhdiyanto, Muhdiyanto; Atul, Lukluk (Universitas Muhammadiyah Magelang, 2010)
Transformasional leadership had identified with leader behavior that more aktified and efektif. This behavior is adviced with give a full motivation to employee, so will give skill to create ekspektasion an employer people and that will motivation with all extra-role behaviour. This aim to research is testing mediating effect at transformasional leadership effect for empowerment organizational citicion behavior in financial institute non bank at magelang religion. Data for this study were collected using a questionnaire survey sent to 240 responden in financial institude at the Magelang. At least 204 employee in financial institute non bank that had participated in this research, also same tp 71% response rate. he study employs a moderated regression Analysis (MRA) to analyze the hiphothesis and assist by the SPSS 12.00 from windows programs. The result of this research is showed that mediating effect at transformasional leadership for organizational citicion behavior significant, and mediating effect empowerment organizational is significant.